Dynamics of CO2 price drivers - Sousa, Rita (2014)
Using data from Phase II-III of the European Union Emission Trading Scheme, we characterize CO2 prices interrelation with energy prices (gas, electricity and coal), carbon allowances substitute prices and with economic activity index. We estimate a vector autoregressive model and the responses of CO2 prices to impulses in other variables, observing duration and direction of the impact. Our main findings include significant positive impact of returns in CO2 of peak electricity, gas, and economy index, and CO2 returns itself. The impact is visible during ten days in case of an electricity innovation, and during one day in case of gas. A shock in economy index prices has 2 days impact, and finally a substitute good for carbon licences in the European market does not have a significant impact.